USE TECHNOLOGY LEARNING TO CHALLENGE CURRENT PROFESSIONAL KNOWLEDGE - Dinara Saitxxanova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Many technological resources offer to learn reports, helping faculty to identify, individually or collectively, where the subject matter is the most successful in which students need to study more.In addition, the current situation surrounding the Covid-19 virus, which greatly affected how teachers around the globe work, has influenced the teaching environment and turned it into a virtual reality, where many teachers and lecturers are forced to work with more innovative programmers such as, Zoom, Loom, Learn-Cube and so on, which let them present classes to students, while applying strategies aimed at reducing anxiety.